1998
DOI: 10.1029/98jc01265
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic loading and creep response of aligned first‐year sea ice

Abstract: Abstract. Characteristics such as brine and gas porosity and crystallographic features can have a profound impact on the mechanical properties of first-year sea ice. These characteristics vary spatially and temporally, and it is important in the development of constitutive models to address their variability in physically meaningful terms. A program of laboratory experiments on field cores of first-year sea ice has been conducted to aid in the development of such models. A thorough assessment of the bulk physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Here, we attribute pre-melt films developing at triple-junctions or on grain boundaries as the dominant mechanism for the changes in the values of the elastic properties and wave attenuation as a function of ice temperature. This is a more likely contributor than the dislocation damping mechanisms proposed to dominate at the highest temperatures (Cole et al, 1998;Cole, 1990;Cole andDurell, 1995, 2001;McCarthy and Cooper, 2016) since these samples have not been subject to deformation. This has been observed previously by Spetzler and Anderson (1968) and Kuroiwa (1964) in laboratory resonant bar measurements and in the field at seismic frequencies (Peters et al, 2012).…”
Section: Temperature Dependence and Pre-meltmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we attribute pre-melt films developing at triple-junctions or on grain boundaries as the dominant mechanism for the changes in the values of the elastic properties and wave attenuation as a function of ice temperature. This is a more likely contributor than the dislocation damping mechanisms proposed to dominate at the highest temperatures (Cole et al, 1998;Cole, 1990;Cole andDurell, 1995, 2001;McCarthy and Cooper, 2016) since these samples have not been subject to deformation. This has been observed previously by Spetzler and Anderson (1968) and Kuroiwa (1964) in laboratory resonant bar measurements and in the field at seismic frequencies (Peters et al, 2012).…”
Section: Temperature Dependence and Pre-meltmentioning
confidence: 99%
“…It is well understood that porosity, dislocation structures, the configuration of grain boundaries, and any crystallographic preferred orientation textures play an important role in the absolute value of visco-elastic dissipation (McCarthy and Castillo-Rogez, 2013;Cole et al, 1998) and elastic wave speeds (Maurel et al, 2015;Diez and Eisen, 2015;Gusmeroli et al, 2012) in ice.…”
Section: Temperature Dependence and Pre-meltmentioning
confidence: 99%
“…Dynamic studies on non-deformed and annealed samples of polycrystalline ice have confirmed the presence of an attenuation peak at high temperatures attributed to grain boundary sliding (Cole et al 1998). Interestingly, samples that were strained to 1% showed an increase in the high-temperature background attenuation that caused the grain boundary peak to nearly disappear (Tatibouet et al 1987).…”
Section: Grain-boundary Sliding (Gbs)mentioning
confidence: 83%
“…More recently, the significant bulk of work on dissipation in both laboratory grown and natural sea ice to date has been conducted by David Cole and various coworkers (e.g. Cole 1995Cole , 2001Cole et al 1998;Durell 1995, 2001). A key contribution from Cole (1995) is the development of an empirically-based model to describe relaxation in ice that is specifically tied to microstructure and defect state.…”
Section: Brief History Of the Research On Ice Attenuation Propertiesmentioning
confidence: 99%
See 1 more Smart Citation